Peran Konseling Individu dalam Mengatasi Trauma Akibat Kecelakaan Lalu Lintas - Hamdal Afgani Dalimunthe; Ainul Mardiyah; Maulida Ar Rahma; Selvira Amanda (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
Traffic accidents not only cause physical injuries but also significantly impact the psychological state of victims, such as trauma, anxiety, excessive fear, and other emotional disturbances. Post-accident psychological trauma can hinder daily activities and reduce the victim's quality of life if not properly treated. This study aims to examine the role of individual counseling in assisting the recovery process of psychological trauma in traffic accident victims. The study used a qualitative approach with a phenomenological design with three informants who were traffic accident victims and experienced psychological trauma. Data collection was conducted through in-depth interviews to explore the victims' subjective experiences during the recovery process. The data obtained were analyzed using thematic analysis techniques. The results of the study indicate that individual counseling plays a significant role in helping victims recognize and manage negative emotions, reduce anxiety and fear levels, and rebuild a sense of security, self-confidence, and adaptability. Thus, individual counseling is an effective intervention in supporting the ongoing psychological recovery of traffic accident victims.